Meningkatkan Kemampuan Passing Bawah Bola Voli Melalui Model Pembelajaran 4 on 4 pada Siswa Kelas VIII SMP 8 Batu Satu Atap di Kabupaten Sidrap - Andi Febi Irawati; Irwin Irwin; Andi Muh Fatwa Ananta Anshar (Departement of Mathematics Education, 2024)
This type of research uses classroom action research, namely research conducted in class with the aim of improving the basic technique of passing under volleyball through the 4 on 4 playing method. The subjects of this study were students of class VIII of SMP 8 Batu Satu Atap Sidenreng Rappang, with a total of 10 students. The instrument in this study was an assessment rubric to measure the ability of passing under volleyball. The data collection technique used in this study used several guidelines that can be used in Classroom Action Research (PTK), namely observation, literature, and assessment rubrics. The data analysis technique used in this study used the formula used for classical completeness. The learning outcomes of passing under volleyball in cycle I in the complete category were 30%, which amounted to 3 people. In cycle II, there was an increase in the percentage of students' learning outcomes of passing under volleyball in the complete category by 80% with the number of students who completed being 8 students, an increase in student learning outcomes in volleyball games through variations in learning methods of playing 4 on 4 cycle I to cycle II was achieved.